Karakteristik Penderita Syok Kardiogenik - Dinda Dwi Anggreni (Syntax Idea)
Cardiogenic shock (CS) is a condition characterized by low cardiac output despite adequate intravascular volume, leading to end-organ hypoperfusion and death. The causes of cardiogenic shock include myocardial or pericardial damage, disturbances in the heart's conduction system, and disorders of heart valves. Shock is marked by decreased oxygen supply and/or increased oxygen consumption or inadequate oxygen utilization, resulting in cellular and tissue hypoxia. The diagnosis of cardiogenic shock is typically based on easily assessable clinical criteria without advanced hemodynamic assessment, although it has previously been recommended to assess cardiac index and pulmonary capillary wedge pressure (PCWP). Cardiogenic shock carries a poor prognosis and is a leading cause of death in acute MI patients. Acute myocardial infarction (AMI) with left ventricular dysfunction is the most common cause of cardiogenic shock. Nearly 80% of AMIs result in cardiogenic shock complications with mortality rates of 40-50%. Acute myocardial infarction, commonly known as a heart attack, is one clinical manifestation of coronary heart disease. Acute myocardial infarction is the sudden, severe ischemic damage to myocardial tissue. The occurrence of cardiogenic shock carries a higher risk in women. Studies examining gender-specific differences in the management and outcomes of patients with AMI indicate that women are typically older, have greater comorbidities, and are less likely than men to receive guideline-directed therapy and timely revascularization.